Empowering Women in Making Nuggets and Cakes from Yellow Sweet Potatoes and Cencaru Fish in Babalan District, Langkat Regency - Siagian, Albiner; Rochadi, Kintoko (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The nuggets that have been made from chicken and vegetables have not utilized local potentials with high nutritional content and are relatively cheap, namely Cencaru fish and yellow sweet potato. Yellow Sweet Potatoes contain nutrients that are good in energy, protein, carbohydrates, fats, calcium, phosphorus and iron. In Babalan Subdistrict, Langkat Regency, many fish products have not been used optimally in an effort to improve the nutritional status of the community. One of the fish that is cheap but is less attractive to the community while its availability is a lot of cencaru fish (Megalaspis cordyla). In this area there are women who process snacks such as nuggets, noodles, but not yet varied. For this reason, women's empowerment was carried out in producing nuggets and yellow sweet potato cakes and cencaru fish. Through increasing the knowledge and skills of women in producing nuggets and yellow sweet potato cakes and cencaru fish, they become healthy, highly nutritious, inexpensive and cheap school food snacks, starting from production, packaging and marketing. Based on this, the activities of women's empowerment services in the manufacture of nugget and yellow sweet potato and cencaru fishes increase the knowledge and skills of partners in processing nugget and yellow sweet potato and cencaru fish cakes.